An assessment of pluvial hazard in South Jakarta based on land-use/cover change from 2016 to 2022 - Yosua, Horas; Kusuma, Muhammad Syahril Badri; Nugroho, Joko (Frontiers in Built Environment, 2024)
South Jakarta is a megapolitan city that is directly affected by Land Use Cover Change (LUCC). One of the impacts that arise is urban flooding, otherwise known as pluvial floods. More work is needed to evaluate the effect of LUCC on the increase of pluvial floods in South Jakarta. In this study, the runoff coefficient value (C) caused by LUCC is determined and the hazard risk of pluvial floods is evaluated. The analysis uses linear regression classification of LUCC using GIS software and carries out hazard and risk analysis based on Minister of Public Works Regulation Number 12 of 2014. Based on the rational method flood discharge formula, the higher C value result in the greater flow rate in a watershed. To simplify the calculation, the C equivalent value used is the C value that represent the watershed. The growth of the runoff coefficient (C) in South Jakarta is 1 – 1.3% per year. It is found that the rate of increase in the runoff coefficient (C) is the same as the population growth rate of DKI Jakarta, which is around 1.3% per year. The increasing of runoff coefficient also increases the risk of pluvial flooding in locations that are prone to flooding. Furthermore, the hazard risk study found that there are 2 locations with a moderate level on the hazard risk index, namely Ciledug Seskoal and Dharmawangsa Taman Gajah. This study can be used by government agencies as a basis to construct the spatial prioritization framework for pluvial flood mitigation.